Ethè discursifs africains au bord de la Seine. L’exemple de Fatou Diome (Altre Modernità, 2020)
The analysis of enounciative subjectivity in Fatou Diome’s works allows us to focus on the contemporary French-Parisian literary landscape, and on the strategies of locating African writers, or of African descent, within the field. The use of stereotypes about the African writer, and of the exotic discourse emanating from the doxa, reveal that contemporary authors are forced to develop discursive and media strategies to negotiate a place of legitimacy in the French literary field that overlaps partly with the Francophone and worldwide field, but whose objectives and the public reception are not always shared. Fatou Diome’s case study enables discursive analysis on rhetorical ethè, and on how she manages the fictional and mediatical “I”. But it also sheds light on the use of “us” in her pamphlet Marianne porte plainte! that may refer to different communities. The identification of effective positions taken on by the author will then enable us to appreciate the potential for transformation with regard to the consecration and canonisation processes governed by the “center” institutions. The “African” character attributed to both authors and literary productions is the main issue. It remains to be seen whether and how writers who claim literary autonomy are willing to play the “difference” card to satisfy the public who is structurally close to the dominant discourse.
Keywords: Africa; Literary field; Ethos; Posture; Stereotypes; Migrations